Effectiveness of a nanoemulsion formulation of Piper aduncum L. extract and Cymbopogon nardus L. hydrosol in controlling the main pests of broccoli: Efektivitas formulasi nanoemulsi ekstrak Piper aduncum L. dan hidrosol Cymbopogon nardus L. untuk pengendalian hama utama tanaman brokoli - Eka Candra Lina; Arneti; Joko Prasetyo (Jurnal Entomologi Indonesia, 2026)
A nanoemulsion formulation of a mixture of Piper aduncum extract and Cymbopogon nardus hydrosol was evaluated for its effectiveness against the major broccoli pests, Crocidolomia pavonana and Plutella xylostella. The study was conducted in Alahan Panjang, West Sumatra, using a completely randomized design with four treatments (the nanoemulsion formulation, Bacillus thuringiensis, cypermethrin, and a control) and seven replications. Treatments were applied weekly from 21 to 70 days after planting (DAP). Larval population density and plant damage were recorded, and the data were analyzed using analysis of variance (ANOVA) followed by a least significant difference (LSD) test at a 5% significance level. Infestation by P. xylostella occurred earlier at 21 DAP, whereas infestation by C. pavonana began at 28 DAP. Overall, the population density of P. xylostella was higher than that of C. pavonana. The nanoemulsion formulation exhibited insecticidal activity, although its effectiveness was lower than that of cypermethrin and B. thuringiensis. The effectiveness rates against C. pavonana were 71.49%, 48.54%, 33.33%, and against P. xylostella were 73.49%, 60.88%, and 57.52% for cypermethrin, B. thuringiensis, and the nanoemulsion formulation, respectively.